A high‐quality functional genome assembly of Delia radicum L. (Diptera: Anthomyiidae) annotated from egg to adult. (23rd February 2022) - Sontowski, Rebekka; Poeschl, Yvonne; Okamura, Yu; Vogel, Heiko; Guyomar, Cervin; Cortesero, Anne‐Marie; van Dam, Nicole M.
Abstract: Belowground herbivores are overseen and underestimated, even though they can cause significant economic losses in agriculture. The cabbage root fly Delia radicum (Anthomyiidae) is a common pest in Brassica species, including agriculturally important crops, such as oilseed rape. The damage is caused by the larvae, which feed specifically on the taproots of Brassica plants until they pupate. The adults are aboveground‐living generalists feeding on pollen and nectar. Female flies are attracted by chemical cues in Brassica plants for oviposition. An assembled and annotated genome can elucidate which genetic mechanisms underlie the adaptation of D . radicum to its host plants and their specific chemical defences, in particular isothiocyanates. Therefore, we assembled, annotated and analysed the D . radicum genome using a combination of different next‐generation sequencing and bioinformatic approaches. We assembled a chromosome‐level D . radicum genome using PacBio and Hi‐C Illumina sequence data. Combining Canu and 3D‐DNA genome assembler, we constructed a 1.3 Gbp genome with an N50 of 242 Mbp and 6 pseudo‐chromosomes. To annotate the assembled D . radicum genome, we combined homology‐, transcriptome‐ and ab initio‐prediction approaches. In total, we annotated 13, 618 genes that were predicted by at least two approaches. We analysed egg, larval, pupal and adult transcriptomes in relation to life‐stage specific molecular functions. This high‐quality annotated genome of D . radicum is a first step to understanding the genetic mechanisms underlying host plant adaptation. As such, it will be an important resource to find novel and sustainable approaches to reduce crop losses to these pests. Zusammenfassung: Obwohl unterirdische Herbivoren einen erheblichen wirtschaftlichen Verlust in der Landwirtschaft verursachen können, werden sie übersehen und unterschätzt. Die Kleine Kohlfliege Delia radicum (Anthomyiidae) ist ein weit verbreiteter Schädling auf Brassica‐Arten, darunter sind auch wichtige Nutzpflanzen, wie der Raps. Der Schaden wird von den Larven verursacht, die bis zur Verpuppung ausschließlich an den Pfahlwurzeln der Brassica‐Pflanzen fressen. Die adulten Fliegen sind oberirdisch‐lebende Generalisten, die sich von Pollen und Nektar ernähren. Die Weibchen werden von chemischen Signalen der Brassica‐Pflanzen angezogen, wo die Eiablage stattfindet. Ein assembliertes und annotiertes Genom kann Aufschluss über molekulare Mechanismen geben, die der Anpassung von D. radicum an ihre Wirtspflanzen und deren spezifischen chemischen Abwehrstoffe, vor allem Isothiocyanate, zugrunde liegen. Mit einer Kombination aus unterschiedlichen Next‐Generation‐Sequencing‐Methoden und bioinformatischen Ansätzen haben, wir das Genom von D. radicum assembliert, annotiert und analysiert. Wir assemblierten ein D. radicum ‐Genom auf Chromosmenebene unter Verwendung von PacBio und Hi‐C Illumina‐Sequenzdaten. Durch die Kombination von Canu und dem 3D‐DNA Genomassembler konnten wir ein 1, 3 Gbp großes Genom mit einem N50 von 242 Mbp und 6 Pseudo‐Chromosomen erstellen. Für die Annotation des Genoms, haben wir homologie‐ und transkriptom‐basierte und ab initio Gen‐Vorhersagemodelle verwendet. Insgesamt haben wir 13.618 Gene annotiert, die von mindestens zwei der Ansätze vorhergesagt wurden. Weiterhin analysierten wir die Transkriptome von Eiern, Larven, Puppen und adulten Tieren in Bezug auf entwicklungsstadienspezifische molekulare Funktionen. Dieses qualitativ hochwertige annotierte Genom von D. radicum, ist ein erster Schritt zum Verständnis der genetischen Mechanismen, die der Anpassung an Wirtspflanzen zugrunde liegen. Es bildet eine wichtige Ressource für die Entwicklung neuer und nachhaltiger Ansätze zur Verringerung von Ertragsverlusten durch diesen Schädling.